TINJAUAN YURIDIS MORATORIUM REMISI TERHADAP NARAPIDANA TINDAK PIDANA KORUPSI - Ony Rosifany (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2015)
Remission is the right of a prisoner, both adults and children, as prisoners. As stipulated in the Correctional Law. Issuance of Letter of Directorate General of Corrections Ministry of justice and Human Rights Number : PAS – HAM.01.02-42 dated October 31, 2011 regarding the Moratorium on Granting Rights of Prisoners of Corruption and Terrorism has some pros and cons of the various parties.               The main regulation is used as reference in protecting the reghts of prisoners is the Law of the Republic of Indonesia Number 12 Year 1995 about Correctional. And implementing rules relating to the right of prisoners has issued the Goveernment, including the Government Regulation Number 32 Year 1999 about Terms and Procedures for Implementation of the Rights of Prisoners and the Government Regulation Number 28 Year 2006 about Amendment of the Government Regulation Number 32 Year 1999 about Terms and Procedures for Implementation of the Rights of Prisoners. So for the current Moratorium Remissions policy can not implemented until the changes to all laws and regulations governing the remission.